THE EFFECT OF DOMINO LEARNING MEDIA THROUGH THE MAKE A MATCH MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES - Putri Yuni Hemilia; Zainuddin Zainuddin; M. Ridwan M. Ridwan (Indonesian Journal of Educational Science (IJES), 2025)
This study aims to influence the use of Domika learning media through the Make a Match learning model to improve Mathematics learning outcomes. The method used in this research is quantitative research with the type of research Quasi-Experimental Design. This research was conducted at Food I Elementary School and addressed Jl Gate Food Village Paberasan District city Sumenep Kab Sumenep. The research sample consisted of grade III students divided into experimental and control classes. The results of data analysis show that the use of domika media in learning Mathematics has a positive impact on student learning outcomes. Normality and homogeneity tests show that the data is usually distributed and has a homogeneous variance, allowing the use of parametric statistical tests. Hypothesis testing using Baron & Kenny's mediation method revealed a significant influence of using domika media on improving students' learning outcomes. The findings show that in addition to students' initial scores (pretest), the improvement in learning outcomes is also mediated by the effectiveness of the learning methods. The study results conclude that house learning media influences the Make-a-Match model, which has a role in improving student learning outcomes